UTILIZING MIND MAPPING AS ASSESSMENT TOOL FOR READING COMPREHENSION - Iradatul Hasanah; Hermawati Syarif; Ratmanida Ratmanida (English Language Teaching and Research, 2017)
Until now, there are still many students who get difficulty in reading compehension, it is hard for them to gain the essence of information among the overlapping sentences. Therefore, the lecturer provides them strategies to handle it. Among others is mind mapping which facilitates the students in acquiring the important informations of the textbook effectively. The fact shows that mind mapping has been applied in some schools even in higher level of education which is intended to assist students in reading comprehension. However, there is too little attention in assessing it whereas mind mapping can be another alternative assessment tool for reading comprehension. By doing ongoing assessment, mind mapping can provide the lecturer with the information needed to develop appropriate lessons and improve instruction. This article explores on how the to utilize mind mapping as assessment tool rather than just as an assignment for reading comprehension. Key words: mind mapping, assessment tool, reading comprehension